Mosquitocidal potential of Chysophylum africanum seed extracts against human vector mosquitoes Anopheles stephensi (Liston) (Diptera: Culicidae) - Adesina JM1; Jose AR2; Mobolade-Adesina TE2 (Open Journal of Environmental Biology - Peertechz Publications, 2019)
Mosquito borne diseases constitute a major public health problem in the list of communicable diseases, An. stephensi (Liston) is the primary vector of malaria in developing countries and improved methods of control are urgently needed. Larvicidal activity of Chysophylum africanum seed extracts was evaluated against An. stephensi. Fourth instar larvae were exposed to 100, 150 and 200μl concentrations of ethyl acetate, acetone and methanol extracts of C. africanum replicated thrice. Larval mortality was observed at 24 and 48 h after exposure. Results obtained show that the various extracts caused signifi cant mortality effect with increased concentration and duration of exposure, with ethyl acetate extract invoking the maximum mortality (90%) within 24 hours of exposure at all concentrations tested, while acetone recorded the lowest mortality (33.85%) at 200μl. These fi ndings indicate that seeds of C. africanum have larvicidal activity that can be exploited for the management of malaria vector. More studies are needed to determine phytochemical constituents and its mode of action for possible development of larvicides that are safe to use and environment friendly.